Quality changes of Atlantic horse mackerel fillets (Trachurus trachurus) packed in a modified atmosphere at different storage temperatures. (8th February 2013) - Alfaro, Begoña; Hernández, Igor; Baliño‐Zuazo, Lander; Barranco, Alejandro
Abstract Background Atlantic horse mackerel (Trachurus trachurus) is an important commercial fish in Europe. Changes in microbial growth, sensory quality and chemical evolution of modified atmosphere packed (MAP) horse mackerel fillets (48% CO2/50% N2/2% O2) were monitored at different storage temperatures (2, 4, 6 and 10 °C). Results The observed sensory shelf life of MAP fish fillets was found to be approximately 7 days at 2 °C, 6 days at 4 °C, 5 at 6 °C and 3 days at 10 °C. A significant correlation was observed between all sensory attributes and two groups of bacteria [total viable count (TVC) and psychrotrophic bacteria], with sensorial rejection when the bacteria approached 106 CFU g−1 at 4, 6 and 10 °C. A level of 30–50 mg total volatile basic nitrogen 100 g−1 of mackerel muscle was well correlated with sensory shelf life determination at all temperatures, except for 2 °C. During the storage time, lipid oxidation did not increase at any temperature and could not be related to quality decay. The presence of acetaldehyde and butyraldehyde in the packing atmosphere was only found in fillets stored at the highest temperature studied (10 °C). Conclusion In this study, key quality parameters were established to monitor the spoilage and shelf life of MAP Trachurus trachurus stored at different temperatures. In addition, these results confirm the use of modified atmosphere packaging as a mild preservation method for fillets of Atlantic horse mackerel. © 2012 Society of Chemical Industry